1983
DOI: 10.3109/17453678308992917
|View full text |Cite
|
Sign up to set email alerts
|

The Blood Flow of Rabbits' Tendons:Variation with Age, Activity and Hypoxia

Abstract: The Xenon133 washout technique was used to measure the blood-flow rate in flexor tendons of rabbits in different conditions. No variation was found with age. On the other hand, activity caused by electrical stimulation of the muscle increased the flow rate in the tendon significantly, confirming that the tendon is a metabolically active structure. Ligation of the vessels to the tendons failed to achieve a decrease of the blood flow rate. This was probably due to a rapid revascularization or biochemical modific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In recent years, the topic of tendon nutrition (Manske and Lesker 1982;1985) and blood supply (Brockis 1953;Bergljung 1968;Chaplin 1973;Lundborg 1979;Armenta and Lehrman 1980;Piaggi and Mingione 1981;Zbrodowski, Gajisin and Grodecki 1981;1982;Azar, Culver and Fleegler 1983;Gajisin, Abrodowski and Grodecki 1983;Landi, Elves and Piaggi 1983;Hooper, Davies and Tothill 1984) has gained increased emphasis in the medical literature, in particular with regard to surgery and post operative care of the traumatised human digital flexor tendon. The basic principles of nutritional supply and anatomic design have been described in a number of animal models (Bergljung 1968;Chaplin 1973;Manske and Lesker 1982;Landi el al 1983;Kain et a1 1988).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the topic of tendon nutrition (Manske and Lesker 1982;1985) and blood supply (Brockis 1953;Bergljung 1968;Chaplin 1973;Lundborg 1979;Armenta and Lehrman 1980;Piaggi and Mingione 1981;Zbrodowski, Gajisin and Grodecki 1981;1982;Azar, Culver and Fleegler 1983;Gajisin, Abrodowski and Grodecki 1983;Landi, Elves and Piaggi 1983;Hooper, Davies and Tothill 1984) has gained increased emphasis in the medical literature, in particular with regard to surgery and post operative care of the traumatised human digital flexor tendon. The basic principles of nutritional supply and anatomic design have been described in a number of animal models (Bergljung 1968;Chaplin 1973;Manske and Lesker 1982;Landi el al 1983;Kain et a1 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The terminal angiograms confirmed that these elevated absolute temperature patterns correlated anatomically with the sites of hypervascularity. 6 All of the data used to generate rewarm curves were also used to determine the rewarm rates (slopes) for every site and observation period. Exponential, linear, logarithmic, and first-order quadratic fits were examined.…”
Section: Quantitative Analysis Of Transient Thermogramsmentioning
confidence: 99%
“…An early human study reported a reduction of vascularity in the supraspinatus tendons with age (aged 20-70 years) (Brewer, 1979). While there was no change in the rate of blood flow in the flexor tendons with age in a rabbit study (Landi et al, 1983), there was a significant decrease in blood flow in the intratendinous region of rotator cuff of elderly subjects compared with younger subjects (Funakoshi et al, 2010). Rudzki et al (2008) reported a significant decrease in blood flow in intact supraspinatus tendon in asymptomatic subjects older than 40 years compared with younger subjects after exercise.…”
Section: Structural Changesmentioning
confidence: 95%